A summary of peer-reviewed resources for teaching volcanology in higher education - Dohaney, Jacqueline; Jolley, Alison; Kennedy, Ben; Watson, Alex (Volcanica, 2023)
Here, we summarise and categorise the volcanology learning activities identified and described in a systematic literature review of volcanology higher education (a companion article; Dohaney et al. [2023]). We share the 47 peer-reviewed articles organised by useful categories, such as educational level, mode and setting of learning, volcanic phenomena, and skills learned in the curricula for easier use and navigation by volcanology instructors. Based on the claims made in the peer-reviewed resources, considerations and suggestions for improved volcanology teaching are included, e.g. exploring authentic field-based experiences, local sites, or simulated demonstrations of volcanic phenomena. To support use of these curricula, we provide suggestions for adapting the resources and highlight additional online catalogues that house useful and engaging volcanology teaching materials.